Gravitropic Relation of Seedling Emergence in Diploknema Butyracea(Roxb.) H.J. Lam. - Bahar, Nawa (Indian Forester, 2012)
The present investigation was carried out to find the effect of seed orientation on germination behaviour, vigour and other features of the seedling development under laboratory conditions. It was observed that the germination and all the characters of emerged seedling were higher in the horizontal position as compared to the equilibrium (micropyle end of the seed facing towards the centre of gravity) and non-equilibrium (micropyle end of the seed facing skyward position). It is also found that vigour index was four times more in horizontal position as compared to non- equilibrium position.